POTRET DIALOG ANTARAGAMA PEDAGANG KATOLIK DAN MUSLIM DI PASAR INPRES RUTENG - Fransiskus Sales Lega; Marianus Supar Jelahut (Unika Santu Paulus Ruteng, 2021)
Dialogue is a way of being in the Church in a world characterized by religious and cultural diversity. This study aims to explore the interreligious dialogue of the traders at the Inpres Ruteng market. This research is urgent because the Inpres Ruteng market is a miniature of religious pluralism. This research uses a qualitative approach. The main instruments in collecting data were in-depth interviews and observations. The findings of this study indicate that two types of dialogue have been practiced by traders in Ruteng Inpres market, namely the dialogue of life and dialogue of works. These two types of dialogue have become part of the way of life of Catholic and Muslim traders in the Ruteng Inpres market. Two types of dialogue that have not yet appeared are the dialogue of faith experience and the theological dialogue. It is hoped that the strength of the dialogue on life and the dialogue of work is expected to be the strength to create a holistic and integral transformation in the lives of traders in the Ruteng Inpres market. Based on the findings of this study, the following two recommendations should be made. First, faith dialogue and theological dialogue need to be developed in order to build an adequate understanding of the uniques of the teachings of other religions. Developing a dialogue of faith and theological dialogue needs to be facilitated by the leaders of each religion. Second, further research is expected to focus on efforts to portray potential conflicts in the relationship between Catholic traders and Muslims in the Inpres Ruteng market. This is important so that the planning of preventive steps to prevent conflict can be done properly and measured.